Water sorption of CH3- and CF3-Bis-GMA based resins with additives - Anuradha Prakki; Renato Cilli; Ian Matos Vieira; Kristina Dudumas; José Carlos Pereira (University of São Paulo, 2012)
OBJECTIVES: To evaluate the effect of additives on the water sorption characteristics of Bis-GMA based copolymers and composites containing TEGDMA, CH3Bis-GMA or CF3Bis-GMA. MATERIAL AND METHODS: Fifteen experimental copolymers and corresponding composites were prepared combining Bis-GMA and TEGDMA, CH3Bis-GMA or CF3Bis-GMA, with aldehyde or diketone (24 and 32 mol%) totaling 30 groups. For composites, barium aluminosilicate glass and pyrogenic silica was added to comonomer mixtures. Photopolymerization was effected by 0.2 wt% each of camphorquinone and N,N-dimethyl-p-toluidine. Specimen densities in dry and water saturated conditions were obtained by Archimedes' method. Water sorption and desorption were evaluated in a desorption-sorption-desorption cycle. Water uptake (%WU), water desorption (%WD), equilibrium solubility (ES; µg/mm³), swelling (f) and volume increase (%V) were calculated using appropriate equations. RESULTS: All resins with additives had increased %WU and ES. TEGDMA-containing systems presented higher %WU, %WD, ES, f and %V values, followed by resins based on CH3Bis-GMA and CF3Bis-GMA. CONCLUSIONS: Aldehyde and diketone led to increases in the water sorption characteristics of experimental resins.